Pengaruh Hoaks Politik di Media Sosial Terhadap Perilaku Memilih Pemilih Pemula pada Pemilu 2024 - Puti Meilia, Wike; Eka Putri, Nora (PUBLICNESS: Journal of Public Administration Studies, 2025)
This study analyzes political hoaxes' influence on novice voters' behaviour in the 2024 elections in Solok Regency. Using a quantitative approach with a survey method, this study involved a sample of novice voters in Solok Regency selected by systematic randomization. Data analysis used simple linear regression by adopting Allcott & Gentzkow's theoretical framework on hoaxes and hatred. The results showed a significant effect of political hoaxes on the behaviour of novice voters, with a coefficient of determination of 0.235 (23.5%). This indicates that 23.5% of the variation in the behaviour of first-time voters can be explained by exposure to political hoaxes, while 76.5% is explained by other factors not studied. The significance of this relationship is confirmed by the p-value = 0.019 (<0.05) and the t-count value of 5.49, which is greater than the t-table of 1.984. These findings underscore the importance of digital literacy and political education for first-time voters to mitigate the impact of political hoaxes in the democratic process.